Hubungan Dukungan Keluarga Dengan Tingkat Stress Pasien Kemoterapi Di Ruang Anggrek Tewu RSUD dr. Murjani Sampit - Karmitasari Yanra Katimenta; Agustina Nugrahini; Hermanto Hermanto; Rabiatul Mahmudah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The support of a cancer patient's family has a significant impact on the experience and treatment outcomes of chemotherapy. Family support encompasses four main dimensions: emotional, esteem, instrumental, and informational. The presence of emotionally supportive family members can reduce stress levels and improve the mental well-being of patients. Cancer patients undergoing chemotherapy often experience feelings of sadness, despair, and a loss of interest in activities. Some even discontinue chemotherapy. This study aims to investigate the relationship between family support and the stress levels of chemotherapy patients in the Anggrek Tewu Room at RSUD dr. Murjani Sampit. This research employs a quantitative research method, a cross-sectional research design, and total sampling technique. The sample consists of 45 individuals. A questionnaire instrument is used, and Spearman Rank statistical test is applied to examine the relationship between family support and the stress levels of chemotherapy patients. The statistical analysis results with Spearman rho show that the ? value is 0.160 where (? = 0.05), so ?>?, thus Ha is rejected, meaning: